Integration of Sequencing and Epidemiologic Data for Surveillance of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Infections in a Tertiary-Care Hospital. (20th July 2022) - Czech-Sioli, Manja; Günther, Thomas; Robitaille, Alexis; Roggenkamp, Hannes; Büttner, Henning; Indenbirken, Daniela; Christner, Martin; Lütgehetmann, Marc; Knobloch, Johannes; Aepfelbacher, Martin; Grundhoff, Adam; Fischer, Nicole
Abstract: Background: The ongoing coronavirus disease 2019 pandemic significantly burdens hospitals and other healthcare facilities. Therefore, understanding the entry and transmission of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is critical for effective prevention and preparedness measures. We performed surveillance and analysis of testing and transmission of SARS-CoV-2 infections in a tertiary-care hospital in Germany during the second and third pandemic waves in fall/winter 2020. Methods: Between calendar week 41 in 2020 and calendar week 1 in 2021, 40%, of all positive patient and staff samples (284 total) were subjected to full-length viral genome sequencing. Clusters were defined based on similar genotypes indicating common sources of infection. We integrated phylogenetic, spatial, and temporal metadata to detect nosocomial infections and outbreaks, uncover transmission chains, and evaluate containment measures' effectiveness. Results: Epidemiologic data and contact tracing readily recognize most healthcare-associated (HA) patient infections. However, sequencing data reveal that temporally preceding index cases and transmission routes can be missed using epidemiologic methods, resulting in delayed interventions and serially linked outbreaks being counted as independent events. While hospital-associated transmissions were significantly elevated at a moderate rate of community transmission during the second wave, systematic testing and high vaccination rates among staff have led to a substantial decrease in HA infections at the end of the second/beginning of the third wave despite high community transmissions. Conclusions: While epidemiologic analysis is critical for immediate containment of HA SARS-CoV-2 outbreaks, integration of genomic surveillance revealed weaknesses in identifying staff contacts. Our study underscores the importance of high testing frequency and genomic surveillance to detect, contain and prevent SARS-CoV-2–associated infections in healthcare settings. Abstract : A combination of genomic variant analysis and person-to-person contact tracing reconstructs entry of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) into a tertiary-care hospital from the community and identifies index patients and cryptic transmissions in hospital outbreaks. Vaccination and systematic polymerase chain reaction testing reduced hospital-associated SARS-CoV-2 infections.